Research on an optimal QoS DBA implement mechanism of EPON multicast - ZHANG Jin-yu1; YANG Wei1; LIU Li3 (Tongxin xuebao)
By referring to economic mode,a QoS priority algorithm for EPON multicast was introduced based on its network attribute,user attribute and market attribute.Based on the multicast QoS priority,the network bandwidth was dynamically allocated among multicast services.It could overcome the disadvantages of lower benefit and higher loss rate of package in the network-priority-based QoS mechanism.It effectively reduced delay jitter of package by reshaping the variable-length and disorderly Ethernet downstream frame into the constant-length and orderly one.The simulation result verifies its merits well.